2011
DOI: 10.1073/pnas.1107784108
|View full text |Cite
|
Sign up to set email alerts
|

Lte1 promotes mitotic exit by controlling the localization of the spindle position checkpoint kinase Kin4

Abstract: For a daughter cell to receive a complete genomic complement, it is essential that the mitotic spindle be positioned accurately within the cell. In budding yeast, a signaling system known as the spindle position checkpoint (SPOC) monitors spindle position and regulates the activity of the mitotic exit network (MEN), a GTPase signaling pathway that promotes exit from mitosis. The protein kinase Kin4 is a central component of the spindle position checkpoint. Kin4 primarily localizes to the mother cell and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…More recent experiments revealed that Lte1, a possible Etd1 budding yeast homolog (Garcia-Cortes and McCollum 2009), rather than acting as a GEF, contributes to the proper localization of MEN regulators such as the Bfa1 GAP (Geymonat et al 2010) and the Kin4 kinase (Falk et al 2011). Given that the removal of Rga1 or Rga5 Rho1 GAPs mimics Etd1 function ( Figure 1D), we hypothesize that Etd1 binding to Rho1 ( Figure 3D and Figure 4D) may activate this GTPase by competing for binding of its negative regulators.…”
Section: Etd1 a Novel Activator Of Rho1mentioning
confidence: 99%
“…More recent experiments revealed that Lte1, a possible Etd1 budding yeast homolog (Garcia-Cortes and McCollum 2009), rather than acting as a GEF, contributes to the proper localization of MEN regulators such as the Bfa1 GAP (Geymonat et al 2010) and the Kin4 kinase (Falk et al 2011). Given that the removal of Rga1 or Rga5 Rho1 GAPs mimics Etd1 function ( Figure 1D), we hypothesize that Etd1 binding to Rho1 ( Figure 3D and Figure 4D) may activate this GTPase by competing for binding of its negative regulators.…”
Section: Etd1 a Novel Activator Of Rho1mentioning
confidence: 99%
“…Spindle misalignment errors that result in the retention of both SPBs in the mother cell place these two SPBs in the zone of high Kin4 activity that drives Kin4 onto both SPBs to block mitotic exit. If one SPB eventually enters the bud, Kin4 activity will be inhibited on that SPB bud by Lte1 to promote Kin4 departure and so drive MEN activation from this SPB bud (Bertazzi et al 2011;Falk et al 2011;Caydasi et al 2014). …”
Section: Extrinsic Control Of Asymmetric Spb Behavior Drives the End mentioning
confidence: 99%
“…The protein kinase Kin4 functions in opposition to Cdc5, phosphorylating Bfa1 and thus rendering the GAP insensitive to Cdc5-dependent inhibitory phosphor-ylation (Maekawa et al 2007). Tem1 is positively regulated by Lte1, which inhibits Kin4 in the bud (Bertazzi et al 2011;Falk et al 2011).…”
mentioning
confidence: 99%